1988
DOI: 10.1099/0022-1317-69-9-2229
|View full text |Cite
|
Sign up to set email alerts
|

Varicella-Zoster Virus DNA from Persistently Infected Cells Contains Novel Tandem Duplications

Abstract: SUMMARYA persistent infection with varicella-zoster virus was established in the Mewo human melanoma cell line. This persistently infected cell line went through periodic crises of virus-induced cell killing and then recovery. Analyses of viral DNA derived from the persistently infected cultures revealed that novel viral nucleic acid rearrangements had been generated. These viral DNA sequences were derived from a specific region of the inverted repeat sequence of the genome flanking the short unique genome seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In addition intra-clade diversity has been calculated to be 0.03-0.07% or 1 in 1429-1 in 3333 bases, using sequences from 8 clade 1 viruses [13]. Whole genome sequencing also confirms early experiments showing recombination between different strains [3,14]…”
Section: Introductionmentioning
confidence: 62%
“…In addition intra-clade diversity has been calculated to be 0.03-0.07% or 1 in 1429-1 in 3333 bases, using sequences from 8 clade 1 viruses [13]. Whole genome sequencing also confirms early experiments showing recombination between different strains [3,14]…”
Section: Introductionmentioning
confidence: 62%
“…The ability of herpesviruses to establish persistent infection has been well documented (10,13,14,31,39,48). Numerous studies from our laboratory have demonstrated that DIPs of EHV-1 mediate persistent infection (2,3,8,11,26,35,41).…”
Section: Discussionmentioning
confidence: 99%
“…While some investigators have documented changes in VZV restriction profiles on serial passage (11,12,20,45,47), others failed to observe any differences after as many as 33 passages in cultured cells (20,45). The serial passage of the Oka parental virus in tissue culture resulted in a well-documented accumulation of mostly single point mutations (20).…”
mentioning
confidence: 99%